Perbandingan Metode TOPSIS Dan SAW Sebagai Sistem Pendukung Keputusan Dalam Menentukan Supplier Bahan Baku - Sari, Hasna Yustika; Salma Salsabila, Andini; Pramita Widyassari, Adhika (Jurusan Informatika STTR Cepu, 2024)
Choosing the right supplier is crucial for operational success in the era of globalization, as errors in supplier selection can negatively impact product quality, costs, and customer satisfaction. XYZ Company, engaged in the food processing sector, faces challenges in optimally selecting raw material suppliers. The Decision Support System (DSS) employs the Simple Additive Weighting (SAW) method and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) to aid this process, where SAW offers simplicity and ease of implementation, while TOPSIS provides a more comprehensive assessment by considering the relative distance to positive and negative ideal solutions. This study compares the effectiveness of SAW and TOPSIS in supplier selection at XYZ Company, providing insights into the strengths and weaknesses of each method and serving as a reference for other companies facing similar challenges.